Midwife's knowledge level and delivery ball techniques on labor pain - idawati; Ningsih, Aulia; Juliyanti, Arlina; Ervina; Zahara, Rita (Trigin Institute, 2023)
Childbirth is a natural process and causes pain caused by contractions when the mother is giving birth. One of the non-pharmacological methods that can be used is the birth ball method, which is a method of using a rubber ball filled with air to reduce back pain during pregnancy and childbirth which is safe to use. The method used in this study is a literature review by examining 20 articles with the same topics and themes in the 2018-2023 range from Indonesia. The literature search used the keywords, namely, Childbirth Ball, Labor Pain, Knowledge. Each article is reviewed first, where the article raised is the most relevant. The results obtained from this literature study are that there is an effect of the application of the birth ball method to reduce the intensity of labor pain before and after being given the birth ball method. Based on the results of the discussion conducted by reviewing 20 articles related to the level of knowledge of midwives and labor ball techniques to reduce pain. It can be concluded that there is a significant reduction in pain after being given and implemented birth ball therapy for maternity mothers and the level of knowledge of midwives is high on the use of birth ball therapy